microRNA-146a Signaling in Alzheimer's Disease (AD) and Prion Disease (PrD) - Lukiw, Walter J. (Frontiers in Neurology, 2020)
The mouse- and human-brain-resident, nuclear factor kappa B (NF-κB)-regulated, micro RNA-146a-5p (miRNA-146a-5p) is an inducible, 22 nucleotide, single-stranded non-coding RNA (sncRNA) easily detected in several brain and immunological cell types, and an important epigenetic modulator of inflammatory signaling and the innate-immune response in several neurological disorders. Amongst all studied microRNAs, miRNA-146a-5p (typically referred to as just miRNA-146a) has been well characterized and its pathological function in progressive, age-related and lethal human inflammatory neurodegenerative disease states is well documented. This short communication will review our current understanding of miRNA-146a, its induction by the NF-kB-stimulating actions of inflammatory mediators, including the secretory products of certain microbial species such as viral vectors, and Gram negative bacteria (such as Bacteroides fragilis) that are normal residents of the human gastrointestinal (GI) tract microbiome, and how miRNA-146a appears to contribute to neuro-pathological, neuro-inflammatory and altered neuro-immunological aspects of both Alzheimer’s disease (AD) and prion disease (PrD).Alzheimer’s disease (AD); herpes simplex virus; microRNA (miRNA); miRNA-146a-5p; NF-kB (p50/p65); prion disease (PrD); microbiome